APLIKASI SISTEM PENDATAAN BARANG HABIS PAKAI GUNA MENINGKATKAN KUALITAS STOK BARANG PADA PT. ANGKASA PURA II TANGERANG - Ruli Supriati; Astri Wulan Sari (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
The warehouse is one of the places used to store the company's goods (assets). In general, the process of collecting used goods in carrying out activities of recording of expired goods in PT Angkasa Pura II Soekarno - Hatta Airport is still semi computerized that is using the manual form and Microsoft Excel software. The trouble encountered in conducting this research is matters occurring in collecting used goods that is numberization of Goods Received Goods Receipts (BAPBBP). This study aims to design the system of recording of goods used in PT Angkasa Pura II. The analytical method used is SWOT to analyze the problems of internal and external company. this method is also used to perform analysis of running procedures and systems, related to data collection of consumables and auctions. The design method uses UML (Unified Modeling Language). It is expected to develop information that can be used to manage the data of used goods and inventory quantities well that can produce information accurately, quickly, and appropriately for warehouse management in PT. Angkasa Pura II in the future.